Application of Groundwater Sampling and Insitu Tests Technology in Defining the Seawater Intrusion Into Coastal Aquifer System - Tajul Baharuddin, Mohamad Faizal; Yusoff, Nor Azizi; Embong, Zaidi; Lim, Alvin John Meng Siang (Penerbit UTHM, 2020)
Application of groundwater sampling and insitu tests technology is used to identify the subsurface hydrogeology characteristics of the seawater intrusion condition into coastal aquifer system. The subsurface hydrogeology characteristics studies involved identifying subsurface hydrogeology materials, effects of groundwater tables to the seasonal patterns and groundwater quality of the coastal aquifer. The studies will be providing information on the types of material in geology deposits and bedrocks. The types of aquifer in the study area can be identified after the material types of the subsurface hydrogeology have been determined.